PENGARUH PENERAPAN GOOD GOVERMENT GOVERNANCE DAN KINERJA APARATUR DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA SE-KECAMATAN LASALIMU - Pardana, Deki; Intan, Nur (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
This study aims to examine the effect of good government governance and the performance of village apparatus on the accountability of managing village funds, using descriptive quantitative analysis, using multiple linear regression analysis in SPSS. The results of the study show while the performance of village apparatus has a positive effect on the accountability of managing village funds, it can be seen in the results of the partial test (t test) with a significance value of 0.00 < 0.05, and where this shows a positive direction which can be seen in the calculated t value of 5.596 greater than the t-table of 1.998. And two independent variables simultaneously (together) have a positive effect on village fund management accountability, which can be seen from the significance value of the simultaneous test (f test) where the significance value is 0.00> 0.05, or Fcount is greater than ftable. Where the positive direction shows that the Fcount value is 32.248 while the ftable is 3.15. While the level of influence between the independent variables on the dependent variable can be seen from the adjusted R Square value of 0.298 or 29.8%. This indicates that the accountability variable for village fund management can be influenced by good government governance variables and village apparatus performance variables by 29.8%, while the remaining 70.2% is explained by other variables not present in this study.